The Influence of Leadership and Co-Worker Relationships on Employee Productivity at the Main Clinical Laboratory of Siaga Medika Jakarta - Mardhiko, Arief; Zaharuddin, Zaharuddin; Supriyadi, Supriyadi (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the influence of leadership and co-worker relationships on employee productivity within the work environment of the Main Clinical Laboratory at Siaga Medika Jakarta. The research employs a quantitative approach using regression analysis, with 15 employees serving as respondents. Data collection was conducted through a structured questionnaire, which was tested for validity and reliability to ensure the accuracy of the findings. The results indicate that both leadership and co-worker relationships have a positive and significant impact on employee productivity. These findings suggest that effective leadership contributes to a structured and motivational work environment, while harmonious co-worker relationships foster collaboration and teamwork, ultimately enhancing overall organizational productivity.